Fly ash for the treatment of Zn(II) rich effluents - Singh A.K.; Singh D.P.; Singh V.N. (My University, 2025)
The ability of fly ash to remove Zn(II) from water by adsorption has been tested at different concentrations, temperatures and pH of the solution. It was found that low adsorbate concentration, small particle size of adsorbent and higher temperature favoured the removal of Zn(II) from aqueous solution. The Langmuir isotherm was used to represent the equilibrium data at different temperatures. The apparent heat of adsorption has been found to be 17.325 Kcal mol-1, which indicates the process to be endothermic. The uptake of Zn(II) is diffusion controlled and the mass transfer coefficient is 3.56 × 10-5cm s-1. The maximum removal was noted at pH 7.5. © 1991 Science and Technology Letters.